PENGARUH FEE BASED INCOME TERHADAP PROFITABILITAS PADA BANK MUAMALAT INDONESIA PERIODE 2012-2022 - Septyana, Mutiara; Asnaini, Asnaini; Fryanti, Yunida Een (JURNAL ILMIAH EDUNOMIKA, 2024)
One of the indicators used to measure the performance of a company and measure the amount of profit so that it is used efficiently is to look at the profitability ratio. In terms of profitability, the ratio most often used is Return On Assets (ROA), which measures the ability of bank management to obtain overall profits. The greater the Return On Assets (ROA) of a bank, the greater the level of profit achieved by the bank. The aim of this research is to find out how Fee Based Income influences Bank Muamalat Indonesia's profitability in 2012-2022. This research uses a quantitative approach with data in the form of numbers which will be analyzed and tested using SPSS. The method used is a simple linear regression analysis method, this method is used to determine the influence of Fee Based Income on the Profitability of Bank Syariah Indonesia. The data used is secondary data, namely a time series obtained from Bank Muamalat Indonesia financial report data for 2012-2022. The results of this research indicate that there is no significant influence of the Fee Based Income variable partially on the profitability of Bank Muamalat Indonesia.